2012
DOI: 10.1007/s00264-012-1632-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of chronic groin pain in athletes

Abstract: Purpose Conservative treatment of chronic groin pain is prolonged and recurrence is quite common. Coexistence of sports hernia and adductor tendinitis/tendinosis in a single patient is noted in the literature. In our study we evaluated our operative treatment that should enable pain elimination and fast return to sports activities. Methods We performed a prospective study over a six-year period. Ninety-nine (99) patients, all male, with chronic groin pain, resistant to conservative treatment, underwent a surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 23 publications
0
13
0
3
Order By: Relevance
“…The cause is yet rather unknown, also reflected by different treatment recommendations ranging from nonoperative measures to surgical adductor release. 11,27,37,40 In the present FAI cohort, adductor insertion tendinopathy was evident in more than 20% of the cases. The clinical relevance of concomitant adductor tendinopathy is, however, unclear.…”
Section: Discussionmentioning
confidence: 88%
“…The cause is yet rather unknown, also reflected by different treatment recommendations ranging from nonoperative measures to surgical adductor release. 11,27,37,40 In the present FAI cohort, adductor insertion tendinopathy was evident in more than 20% of the cases. The clinical relevance of concomitant adductor tendinopathy is, however, unclear.…”
Section: Discussionmentioning
confidence: 88%
“…All the papers had a common aim of reinforcing the abdominal musculature although there was variability in the description of the exact pathological site. Six abdominal papers also included tenotomy of adductor longus during the procedure 20 49 52 55 59 63. There was a common approach to the adductor surgical papers with release of the adductor longus proximal tendon.…”
Section: Resultsmentioning
confidence: 99%
“…This was particularly evident in patients/athletes who present with pain in the abdominal region where a large spectrum of anatomical pathologies are described and multiple interventions recommended. These include resecting the ilioinguinal or genitofemoral nerve23 52 54 57 which potentially diminishes sensation without addressing the underlying problem. Holmich16 and Jansen et al 77 reported that in many cases, multiple painful structures are isolated at the time of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Тому важливо заохочувати спортсменів дотримуватись правильної тренувальної програми та навчати їх звертатися за медичною допомогою на ранніх стадіях захворювання з метою запобігання розвитку хронізації захворювання [9,10]. Існують консервативні та оперативні методи лікування СПБС, застосування яких залежить від локалізації та стадії захворювання [11][12][13].…”
Section: вступunclassified
“…Позасуглобові та навколосуглобові ушкодження, що пов'язані з тендинопатіями, до стадії дегенеративного розриву підлягають консервативному лікуванню [14,15] або іноді хірургічному [12,16]. Внутрішньосуглобові та інгвінальні ушкодження при СПБС підлягають переважно оперативному лікуванню у зв'язку з неефективністю консервативного, що пов'язано зі структурними змінами в ушкоджених тканинах (розрив суглобової губи кульшової западини, дефект задньої стінки пахвинного каналу тощо) [11,19,20]. З точки зору доказової медицини дані щодо вибору оптимальних способів та методів лікування СПБС досить обмежені для того, щоб робити остаточні висновки [19,20].…”
Section: вступunclassified